1991
DOI: 10.1111/j.1476-5381.1991.tb12532.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of porcine relaxin on contraction, membrane response and cyclic AMP content in rat myometrium in comparison with the effects of isoprenaline and forskolin

Abstract: 1 The longitudinal muscle from the uterus of oestrogen-treated rats was quiescent in Mg-free Krebs solution. Electrical stimulation generated phasic contraction, which was depressed to 35% and 18% by 50 mu and 150 mu porcine relaxin, respectively. 2 The phasic contractions were more strongly depressed to 26% by 50 mu relaxin in solution containing 0.6 mm Mg, and the depression lasted for more than 4 h after the removal of relaxin. During the persisting depression, raising the external Ca to 7.5 mm did not rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…It is well known that the spontaneous electrical activities of longitudinal and circular muscle cells differ in pregnant rat uterus and that circular muscle cells show much higher spontaneous activity than longitudinal muscle cells [17,22,24]. In preliminary experiments, on mid-pregnant rat uterus, we confirmed that spontaneous contractions could be recorded only in the circular muscle, while electrical stimulation was required to generate muscle contractions in the longitudinal layer (K. Okabe, unpublished observations).…”
Section: Introductionsupporting
confidence: 71%
“…It is well known that the spontaneous electrical activities of longitudinal and circular muscle cells differ in pregnant rat uterus and that circular muscle cells show much higher spontaneous activity than longitudinal muscle cells [17,22,24]. In preliminary experiments, on mid-pregnant rat uterus, we confirmed that spontaneous contractions could be recorded only in the circular muscle, while electrical stimulation was required to generate muscle contractions in the longitudinal layer (K. Okabe, unpublished observations).…”
Section: Introductionsupporting
confidence: 71%
“…Our previous data, which demonstrate that relaxin does not increase intracellular levels of cAMP in human lower uterine segment fibroblasts, suggest that the relaxin receptor is not a heterotrimeric G protein-associated receptor (23). Although increased intracellular cAMP concentrations in several cell types are associated with relaxin treatment (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), to date no data have been provided by any studies that demonstrate coupling of a relaxin-receptor complex to a heterotrimeric G protein-coupled receptor.…”
Section: Discussionmentioning
confidence: 97%
“…The structure of the relaxin receptor is unknown, and no complete signaling pathway has been identified. Relaxin action in several cell types is associated with the cAMP/adenylate cyclase/PKA pathway (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, no data that demonstrate coupling of a relaxin-receptor complex to a heterotrimeric G protein have been provided.…”
mentioning
confidence: 98%
“…4). Early studies before receptor identification, showed that treatment with relaxin increased cAMP accumulation in THP-1 cells (Parsell et al, 1996), MCF-7 cells (Bigazzi et al, 1992), the mouse pubic symphysis (Braddon, 1978), uterine strips (Sanborn et al, Relaxin Family Peptide Receptors 1980), uterine longitudinal muscle (Osa et al, 1991) from estrogen-primed rats, and in cultures of human endometrial cells (Fei et al, 1990), human endometrial glandular epithelial cells (Chen et al, 1988), newborn rhesus monkey uterine cells (Kramer et al, 1990), rat myometrial cells (Hsu et al, 1985), and rat anterior pituitary cells (Cronin et al, 1987). The importance of cAMP as a signaling pathway for relaxin was confirmed on RXFP1 deorphanization, because constitutively active mutants of RXFP1 (TM6: D637Y) increased cAMP accumulation in a ligandindependent manner (Hsu et al, 2000.…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%